Non-selective laryngeal reinnervation in a child with unilateral left vocal fold palsy utilizing laryngeal electromyography. Issue 2 (19th February 2019) - Faoury, Morad; Frampton, Steven; Allen, David; Burgess, Andrea; Heathcote, Kate; Ismail-Koch, Hasnaa
Abstract: Introduction: The impact of unilateral vocal fold palsy (UVFP) on quality of life cannot be underestimated. Management may be complicated by difficulty in determining prognosis. Currently, there is no standardized management pathway for UVFP. Surgery is considered when speech and language therapy has not been successful or when there is significant aspiration and dysphonia. Surgical options for UVFP include injection laryngoplasty, thyroplasty and laryngeal reinnervation. Methods: We report the case of a 6-year-old girl with a left UVFP sustained following PDA ligation. She suffered significant voice issues, aspiration and intermittent stridor limiting activities. Following multidisciplinary team reassessment including videofluoroscopy and perceptual and objective voice measures, laryngotracheobronchoscopy (LTB) and laryngeal electromyography (LEMG) with injection of Radiesse into the left vocal fold was undertaken. Consequently, she underwent non-selective laryngeal reinnervation with the aim of providing a permanent solution by the formation of an anastomosis between the ansa cervicalis and the main stump of the recurrent laryngeal nerve (RLN) resulting in improved muscle tone. Results: LEMG indicated no spontaneous recovery. The laryngeal injection allowed for temporary improvement of voice and feeding. Consequently non-selective left laryngeal reinnervation using ansa cervicalis and repeat vocal cord injection was performed. Twelve months following surgery her voice remain greatly improved and there are no feeding issues or aspiration. Conclusion: In this case so far the use of LEMG and laryngeal reinnervation has proved successful. Non-selective laryngeal reinnervation techniques for UVFP may provide a permanent solution and should be considered in children as a management option in suitable cases.